Pojęcie winy w prawie karnym -próba analizy krytycznej na tle ujęcia relacyjnego. W sprawie definicji winy -replika (Wojciech Patryas ) - Rodzynkiewicz, Mateusz (Wydział Prawa i Administracji UAM, 1992)
The article present a critical analysis of two representative concepts of guilt in criminal law (so called normative and psychological theories). In these theories, the definitions of guilt are formulated in the form of classical definitions, i.e. in the way which is not adequate to the semiotic essence of the defined term. From a semiotic point of view "guilt" is a name of a certain relation; hence, the author accepts in principle a so-called relation approach to guilt presented by W. Patryas. However, the author criticizes the selection of elements of the quilt relation proposed by W. Patryas. In a legal sense the term "guilt" retains its sense as long as there exists criminal legislation of a given type. In other words, non-classical definition of the guilt relation should be constructed so that the elements of this relation were: (i) behavior of an offender, and (ii) description of behavior contained in a legislative act, including modalities connected with an offender and with the situation in which he or she acted. Guilt can be ascribed, if there is the relation of accordance between the offenders behavior (extralingual reality) and the description of this behavior. A definition of guilt must therefore be of extralingual character (analogy to A. Tarski's semantic definition of truth). The relation approach to guilt cannot be reconciled with the dogma of degrees of guilt. This may lead either to the rejection of the relation approach, or to the revision of traditional views held by legal doctrine.
The concept of guilt in criminal law - an attempt of a critical analysis in the light of the relation approach